Superconducting heterostructures: From antipinning to pinning potentials - Carreira, Santiago José (2014)
We study vortex lattice dynamics in a heterostructure that combines two type-II superconductors: a niobium film and a dense triangular array of submicrometric vanadium (V) pillars. Magnetic ac susceptibility measurements reveal a sudden increase in ac penetration, related to an increase in vortex mobility above a magnetic field H* (T), that decreases linearly with temperature. Additionally, temperature independent matching effects that occur when the number of vortices in the sample is an integer of the number of V pillars, strongly reduce vortex mobility, and were observed for the first and second matching fields, Hand H The angular dependence of H Hnd H* (T) shows that matching is determined by the normal applied field component, while H* (T) is independent of the applied field orientation. This important result identifies H* (T) with the critical field boundary for the normal to superconducting transition of V pillars. Below H* (T) superconducting V pillars repel vortices, and the array becomes an 'antipinning' landscape that is more effective in reducing vortex mobility than the 'pinning' landscape of the normal V sites above . Matching effects are observed both below and above H* (T) implying the presence of ordered vortex configurations for 'antipinning' or 'pinning' arrays. © 2014 IOP Publishing Ltd.